Inter-linkages in financing sustainable development - Velasquez, Jerry (Animo Repository, 2002)
This policy brief examine how the inter-linkages approach to sustainable development governance can be used to help sustainable development financing more effective and efficient. Inter-linkages is a strategic approach to managing sustainable development that seeks to promote greater connectivity between ecosystems and societal actions. On a practical level, this involves a greater level of cohesiveness among Institutional, environmental issue-based, and development-focused responses to the challenges of sustainable development, and among the range of international, regional, and national mechanism that share this challenge. The key to developing a strong integrated approach to sustainable development is the identification of the inherent synergies that exist between different aspects of the environment and an exploration of the potential for more effective coordination sustainable development issues and our responses to them. In our global effort to establish and maintain sustainable development there is perhaps no more immediate and urgent challenge than that which relates to the question of financing. This brief provides an ouline of the key processes and trends that serve to shape the current financing environment. These include the continuing decrease in official development assistance (ODA) levels and the steady increase of private financial and capital flows into the developing world. Also highlighted is the urgent need to clearly define and delineate an appropriate role for ODA within the broader sustainable development challenge. Another key factor shaping the challenge to provide adequate financing for sustainable development is simply the increasing complexity and urgency of the task at hand. There are for example, an increasing number of private and public actors and stakeholders who are required to play a useful role in governance at all levels of governance, international, regional, national, and local. And while the natural environment is beginning to show even greater signs of stress at all four levels, the gap between the richest and poorest peoples of the world continues to widen. This policy brief provides concrete, practical, examples of how the inter-linkages approach can, or has been, applied to the issue of financing in order to use the above trends to the advantage of sustainable development goals. There are several aspects to this task. First, is to identify new and innovative, public and private, sources of financing at the international, regional, and national levels. Second, is to identify, at the project level, ways in which limited funds can be used to the best advantage. Third, is to examine ways in which the mechanisms that finance sustainable development can be made to be more efficient and effective. Within this brief, each of these aspects is explored in detail and discussed within the specific context provided by selected case studies.